The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/microorganisms8101619
|View full text |Cite
|
Sign up to set email alerts
|

Salt Marsh Elevation Drives Root Microbial Composition of the Native Invasive Grass Elytrigia atherica

Abstract: Elytrigia atherica is a native invasive plant species whose expansion on salt marshes is attributed to genotypic and phenotypic adaptations to non-ideal environmental conditions, forming two ecotypes. It is unknown how E. atherica–microbiome interactions are contributing to its adaptation. Here we investigated the effect of sea-water flooding frequency and associated soil (a)biotic conditions on plant traits and root-associated microbial community composition and potential functions of two E. atherica ecotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 85 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Analysis of similarity (ANOSIM) was used to determine the significance of differences in the bacterial community structure under different planting patterns. The correlation between the host root biomass and the rhizosphere compositional similarity was determined using the Mantel test implemented in the Vegan package in R ( Hernández et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of similarity (ANOSIM) was used to determine the significance of differences in the bacterial community structure under different planting patterns. The correlation between the host root biomass and the rhizosphere compositional similarity was determined using the Mantel test implemented in the Vegan package in R ( Hernández et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our finding that the community composition changes along the land–sea transition zone is in accordance with previous studies on salt marsh microbial communities from the North Sea Islands of Spiekeroog and Schiermonnikoog. While the abundance patterns found in our study differ for some taxa, zonal successions between the upper and lower SM [ 26 ] and between the lower SM and the pioneer zone were detected as well [ 28 ]. A study of a salt marsh chronosequence revealed that a bacterial community composition is strongly associated with the successional stages of the salt marsh and also correlates with short-term seasonal changes in environmental parameters [ 32 ].…”
Section: Discussionmentioning
confidence: 88%
“…While some of the zonation-relevant variables are well described and similar between distant locations, other factors are still not fully understood [ 12 , 55 , 56 ]. However, the co-occurrence of certain bacterial taxa and the specific vegetation of salt marshes hints towards a tight interaction [ 26 , 57 , 58 ]. To what extent a bacterial community composition is a result of the environmental conditions or is a shaping variable within the salt marsh environments remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial communities are the major decomposers in the latter stage of decomposition [ 27 , 28 ]. Studies in salt marsh ecosystems not only consider microbial activity and the recycling of nutrients, but also bacterial [ 29 , 30 ] and fungal diversity [ 20 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%